Neonatal Male Circumcision: Still a Controversy. Issue 4 (July 2017) - Beal, Judy A.
Abstract : Nurses have a vital role in offering information to parents about newborn male circumcision based on current evidence and recommendations from professional organizations such as the American Academy of Pediatrics. Our pediatric nursing expert, Dr. Beal, summarizes the issue, including potential risks, benefits and areas of controversy.